Investigating Learner Perceptions of English as a Foreign Language in Higher Secondary Schools in Nawabshah, Pakistan: A Challenge-Based Approach - Qamarnisa Leghari; Liu Yongzhi; Imran Khan; Mir Mujtaba Laghari; Anila Laghari (Tomorrow's Education Journal, 2024)
English has become the most important language for people to learn, and accordingly, it is above politics. Many people have learned it as a second/foreign language in Nawabshah, Pakistan. It is also heard in business speak across international companies with English having developed this role over time due to the Anglicization of other cultures. Many students find learning English as a Foreign Language (EFL) difficult because of the few similar characteristics it shares with their native tongue. The present research intends to investigate the problems EFL learners encounter and attribute those against them. To accomplish this aim, a survey was carried out with EFL learners in Pakistan to gauge what they find difficult about learning English and the elements that impact their learning. English language learners face many obstacles and visible issues. The results of the study can inform language teaching practices and policies to better support EFL learners in overcoming their difficulties and achieving their language learning goals.